Teoretični pojem uprave - Brezovšek, Marjan (Teorija in praksa, 1996)
Defining the theoretical concept of administration is a complex methodological operation. Traditional doctrines define it from the aspect of political and legal viewpoints. However, modern approaches view it as a complex dynamic administrative system of social regulation. The overall economic and social development, show that managing administrative systems cannot be seen mainly as a marginal social activity based on the legalistic model of administration. The social regulation that public administrative systems are engaged in have for themselves become fundamental social processes. In this aspect administrative social regulation form prerequisite premises for economic efficiency, cultural development and general social prosperity in highly developed industrial and urban environments. The conception of public administration is an integral part of the political system.
Keywords: uprava; upravno pravo; javne službe; javna uprava